Okno osierdziowo-płucne ułatwia operację na bijącym sercu – parametry hemodynamiczne - Juraszyński, Zbigniew; Wojno, Anna; Szatkowski, Piotr; Zieliński, Dariusz; Dzielińska, Zofia; Biederman, Andrzej (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Aim : The purpose of this study was to investigate the efficacy of techniques designed to minimize right heart compression and provide better exposure of the posterior wall vessels during cardiac surgery. Material and methods : The study included 88 elective, low-risk patients with multivessel disease including the circumflex branches. All patients were analysed for changes in haemodynamic parameters. Patients were divided into three groups. In Group I (25 pts), measurements were obtained after exposure of the posterior wall with a pleuropericardial window and Trendelenburg position. In Group II (35 pts), measurements were taken after exposure of the posterior wall using three stabilizations and exposure methods (Octopus, Starfish, and deep pericardial sutures). In Group III (28 pts), measurements were taken after exposure of the posterior wall with a pleuropericardial window, Trendelenburg position, and inotropic support. Results : The most significant changes in all three groups were observed during exposure of the posterior wall, with a considerable reduction in mean arterial pressure, stroke volume index, and cardiac index, and an increase in right atrial pressure. Trendelenburg positioning and opening the right pleura resulted in an increase in mean arterial pressure, stroke volume index, and cardiac index when the posterior wall was exposed. Conclusion : Pleuropericardial window combined with the Trendelenburg manoeuvre might reduce compression of the right ventricle and haemodynamic compromise during anastomoses of posterior wall vessels. This simple technique enhances surgery on the beating heart.